Immunological evidence for interactions between the first, second, and fifth conserved domains of the gp120 surface glycoprotein of human immunodeficiency virus type 1. - Moore, J P (1994)
We have used a combination of genetic and immunological techniques to explore how amino acid substitutions in the second conserved (C2) domain of gp120 from human immunodeficiency virus type 1 (HIV-1) affect the conformation of the protein. It was reported previously (R. L. Willey, E. K. Ross, A. J. Buckler-White, T. S. Theodore, and M. A. Martin. J. Viol. 63:3595-3600, 1989) that an asparagine-glutamine (N/Q) substitution at C2 residue 267 of HIV-1 NL4/3 reduced virus infectivity, but that infectivity was restored by a compensatory amino acid change (serine-glutamine; S/N) at residue 128 in the C1 domain. Here we show that the 267 N/Q substitution causes the abnormal exposure of a segment of C1 spanning residues 80 to 120, which compromises the integrity of the CD4-binding site. The reversion substitution at residue 128 restores the normal conformation of the C1 domain and recreates a high-affinity CD4-binding site. The gp120 structural perturbation caused by changes in C2 extends also to the C5 domain, and we show by immunological analysis that there is a close association between areas of the C1 and C5 domains. This association might be important for forming a complex binding site for gp41 (E. Helseth, U. Olshevsky, C. Furman, and J. Sodroski. J. Virol. 65:2119-2123, 1991). Segments of the C1 and C2 domains are predicted to form amphipathic alpha helices. We suggest that these helices might be packed together in the core of the folded gp120 molecule, that the 267 N/Q substitution disrupts this interdomain association, and that the 128 S/N reversion substitution restores it.